Bioadhesive Chitosan Films Loading Curcumin for Safe and Effective Skin Cancer Topical Treatment - Seila Tolentino; Mylene M. Monteiro; Felipe Saldanha-Araújo; Marcilio Cunha-Filho; Tais Gratieri; Eliete N. Silva Guerra; Guilherme M. Gelfuso (Pharmaceutics)
Background/Objectives: This study aimed to evaluate the safety and efficacy of chitosan-based bioadhesive films for facilitating the topical delivery of curcumin in skin cancer treatment, addressing the pharmacokinetic limitations associated with oral administration. Methods: The films, which incorporated curcumin, were formulated using varying proportions of chitosan, polyvinyl alcohol, Poloxamer® 407, and propylene glycol. These films were assessed for stability, drug release, in vitro skin permeation, cell viability (with and without radiotherapy), and skin irritation. Results: The films demonstrated physical stability and preserved curcumin content at room temperature for 90 days. Drug release was effectively controlled during the first 8 h, with release rates ranging from 51.6 ± 4.8% to 65.6 ± 13.0%. The films also enhanced drug penetration into the skin compared to a curcumin solution used as a control (stratum corneum: 1.3 ± 0.1 to 1.9 ± 0.8 µg/cm²; deeper skin layers: 1.7 ± 0.1 to 2.7 ± 0.2 µg/cm²). A cytotoxicity test on metastatic melanoma cells showed that curcumin at topical doses exerted activity similar to that delivered via the skin. Furthermore, curcumin alone was more effective in inhibiting tumor cells than radiotherapy alone (p < 0.01), with no additional benefit observed when curcumin was combined with radiotherapy. Finally, irritation tests confirmed that the films were safe for topical application. Conclusion: The developed chitosan-based bioadhesive films represent a promising alternative for the topical treatment of skin tumors using curcumin.